Strukturänderungen und die Schwächung der Produktionskapazität in Łódź während der hitlerfaschistischen Okkupation [Structural changes and the weakening of production capacity in Łódź during the Hitler fascist occupation] - Bojanowski, Tadeusz (Studia Historiae Oeconomicae, 1979)
This article examines the profound structural changes in the textile industry of Łódź during the German occupation in World War II. Łódź, which had been a major center of textile production before the war, was systematically transformed and exploited economically after the Nazi takeover. In the first months of the occupation, Polish and Jewish-owned enterprises were expropriated, many were shut down or liquidated, and much of the industrial property was transferred to German owners. The aim of this study is to present the development of the textile industry in Łódź under occupation, with particular focus on the effects of Nazi economic policy on ownership structures, enterprise organization, and production capacity. The analysis is based on archival materials, statistical data from the municipal administration of Łódź, and scholarly literature on Nazi economic practices in the General Government and Wartheland. The study reveals that between 1939 and 1943, the number of active textile enterprises in Łódź dropped from 1,457 to approximately 200. Small and medium-sized businesses were especially affected, as their equipment was either destroyed or transferred to large German-owned factories. This process of concentration led to a significant increase in the proportion of workers employed in large-scale operations. At the same time, many textile factories were converted for the production of war-related goods such as weapons, aircraft parts, or cables—accompanied by the systematic dismantling and destruction of textile machinery. As a result, the total production capacity decreased by approximately 30%, and the state of machinery and industrial infrastructure deteriorated significantly. The long-term economic damage was substantial. The case of Łódź clearly illustrates the destructive logic of Nazi occupation policy toward captured industrial centers.